Concurrent intraosseous cartilaginous lesions in patients with multiple osteochondromas identified on total-body MR imaging - Van der Woude, Henk-Jan; Van der Zwan, Arnard L.; Flipsen, Mark; Welsink, Chantal; Ham, S. John (Skeletal radiology, 2023)
Purpose To assess the prevalence of intraosseous cartilaginous lesions in patients with multiple osteochondromas based on total-body (TB) MRI examinations, used for screening purposes. Subjects and methods Between 2013 and 2020, TB-MRI examinations were performed in 366 patients with proven multiple osteochondromas syndrome, to rule out malignant progression. For this study, presence, or absence of intraosseous central or eccentrical chondroid lesions, defined as lobulated lesions with low signal intensity on T1-weighted images, replacing bone marrow and high signal intensity equal to fluid on T2-weighted images in the bone marrow of the meta-diaphysis of (one of) the long bones, were recorded in the long bones as part of a TB-MRI protocol. Results In 62 patients out of the 366 MO patients (17%), one or more intraosseous chondroid lesions (either enchondroma or atypical cartilaginous tumor) were detected. The age of the patients at time of diagnosis ranged from 17 to 61 years (mean, 36). Size of the lesions varied from 4 to 69 mm (mean, 16.3 mm). The most common location was the proximal femur ( n = 29), followed by the distal femur and proximal humerus ( n = 18 and n = 10, respectively). In nine of the patients with an intraosseous chondroid lesion, a second and/or third TB-MRI were available during the period of evaluation (mean interval, 2.7 years between the exams). In none of these patients increase of these intraosseous lesions was noticed. Conclusion Intraosseous chondroid lesions (enchondroma and ACT) appear to occur more frequently in MO patients than in the general population. TB-MRI allows to detect these, besides the identification of OC with suspicious features.